Pengaruh Penambahan Slag Nikel Dan Cacahan Plastik Terhadap Kekuatan Tekan Paving Block - Huzaifa, Huzaifa; Endriatno, Nanang; Kadir, Abd. (Teknik Mesin Universitas Halu Oleo, 2021)
This study aims to analyze the addition of nickel slag and crushed plastic into the paving block on the compressive strength. Paving blocks were made by conventional methods. Samples were made and tested according to SNI 03-0691-1996 standards. After molded, the paving blocks were dried within 28 days. After that, the materials were placed on a compression test device to determine the compressive strength. The results of the compression test showed that the maximum compressive strength value was owned by sample B with a value of 210.8 kg/cm2 with a volume composition of 25% cement, 5% coarse aggregate, 30% nickel slag, 5% fine aggregate, and 35% crushed plastic. The minimum compressive strength was found in sample A with a value of 129.17 kg/cm2 with a mixture composition of 25% cement, 25% coarse aggregate and 50% fine aggregate. From this study, it was found that there was an increase in the compressive strength of the paving block after the addition of chopped plastic and nickel slag.Keywords: paving block, slag nickel, plastic chopping, compressive strength